Penerapan model pembelajaran quantum learning untuk meningkatkan pemahaman peserta didik pada materi perubahan sosial kelas VI sekolah dasar - Salma Maimun Aqila; Retno Winarni; Supianto Supianto (Didaktika Dwija Indria, 2024)
The purpose of this research are to improve the understanding of students through the application of the Quantum Learning model on the material of socio-cultural changes in the lives of people in class VI SD Negeri Lemahbang, Teter, Simo, Boyolali. This research was conducted in the 2023/2024 school year. The research approach uses a qualitative approach with Classroom Action Research (CAR) methods.The subjects of this study were 15 students in class VI, and a teacher at grade VI SD Negeri Lemahbang. This research used observation techniques, test interviews and documentation. Data analysis adopts data analysis proposed by Miles and Huberman which has three main components, namely data reduction, data presentation and conclusion drawing. The results showed that the application of the Quantum Learning model with learning syntax grow; natural; name; demonstrate; repeat and celebrate showed an increase in students' understanding in each cycle. This is evidenced in the preaction activity of 13.33%, cycle 1 of 46.67% and cycle 3 of 86.67%.